2009
DOI: 10.1093/rheumatology/kep282
|View full text |Cite
|
Sign up to set email alerts
|

Nervous system dysfunction in Henoch-Schonlein syndrome: systematic review of the literature

Abstract: In Henoch-Schönlein syndrome, signs of nervous system dysfunction are uncommon but clinically relevant. This review helps clinicians managing Henoch-Schönlein syndrome with nervous system dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 76 publications
0
48
0
4
Order By: Relevance
“…The initial management of patients with suspected cerebral Henoch-Schönlein syndrome includes control of arterial hypertension, seizures and repair of disordered hemostasis. Some trials with plasmapheresis have also been reported (Garzoni et al, 2009;Chen et al, 2000). Anticoagulation agents are advised in patients with secondary anti-phospholipid syndrome (Abend et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The initial management of patients with suspected cerebral Henoch-Schönlein syndrome includes control of arterial hypertension, seizures and repair of disordered hemostasis. Some trials with plasmapheresis have also been reported (Garzoni et al, 2009;Chen et al, 2000). Anticoagulation agents are advised in patients with secondary anti-phospholipid syndrome (Abend et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic vasculitic neuropathies (SVNs) occur with varying degrees of frequency in numerous vasculitides 2,[5][6][7][8] . Histopathologically proven vasculitic neuropathy has not been reported in Kawasaki disease, Takayasu arteritis, anti-glomerular basement membrane disease or Cogan syndrome 4 .…”
Section: Classification Of the Vasculitidesmentioning
confidence: 99%
“…Therefore, we could rule out the possibility of uremic and hypertensive encephalopathy. Garzoni et al 4 reported that without severe hypertension, the most frequent neurologic manifestations of patients with HSP are altered level of consciousness in 54%, convulsions in 40%, focal neurologic deficits in 26%, visual abnormalities in 22%, and verbal disability in 10% of patients. Our patient admitted with hemiplegia and aphasia together.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In this article, we report a severe neurologic involvement in a four-year-old boy with HSP who was treated with intravenous pulse methylprednisolone and pulse cyclophosphamide, and followed-up for four years without any sequel. …”
mentioning
confidence: 99%
See 1 more Smart Citation